2020
DOI: 10.1021/acsbiomaterials.9b01961
|View full text |Cite
|
Sign up to set email alerts
|

Human-Derived Scaffold Components and Stem Cells Creating Immunocompatible Dermal Tissue Ensuing Regulated Nonfibrotic Cellular Phenotypes

Abstract: Regeneration of large-sized acute and chronic wounds provoked by severe burns and diabetes is a major concern worldwide. The availability of immunocompatible matrix with a wide range of regenerative medical applications, more specifically, for nonhealing chronic wounds is an unmet clinical need. Extrapolating the in vitro tissue engineering knowledge for in vivo guided wound regeneration could be a meaningful approach. This study aimed to develop a completely human-derived and minimally immune-responsive scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…As mentioned earlier in introduction, decellularization and preservation methods can remarkably affect the biomechanical and biological properties of tissue [ 17 , 18 ]. Therefore, it is very important to use an optimal concentration and incubation time point of detergents with successful removal of cells and minimal negative effects on ECM proteins and growth factors [ 17 , 29 ]. In our previous study, we optimized a decellularization procedure for decellularization of amniotic membrane using chemical agents such as EDTA and NaOH [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier in introduction, decellularization and preservation methods can remarkably affect the biomechanical and biological properties of tissue [ 17 , 18 ]. Therefore, it is very important to use an optimal concentration and incubation time point of detergents with successful removal of cells and minimal negative effects on ECM proteins and growth factors [ 17 , 29 ]. In our previous study, we optimized a decellularization procedure for decellularization of amniotic membrane using chemical agents such as EDTA and NaOH [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous HA can provide a moist wound healing environment allowing autolytic debridement 23‐25 . We have reported in vitro tissue engineering of a combination wound care product comprising cell‐less AM, human FIB, and HA, termed as AMFIBHA 26 . The previous study confirmed its hemo‐/cyto‐compatible nature with optimum physicochemical properties and supple dermal tissue regeneration.…”
Section: Introductionmentioning
confidence: 88%
“…The study design ensured the implantation of four samples of each specific type on four different animals. Full‐thickness burn associated damage of skin was confirmed using histological analysis of burnt tissue, as published earlier 26 . For the experiment, prepared the wounds and exposed fresh tissue by surgical debridement of the burnt full‐thickness skin along the wound edges, extending to the panniculus carnosus layer using a sterile scalpel blade before application of the scaffolds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…developed a stable dermal tissue graft with minimal immune responses by combining decellularized AM together with fibrin glue and HA. [ 99 ] For bone tissue engineering, Wu et al. aimed to transform the commonly used bone ECM filler particles derived from porcine thighbones to a hydrogel form that was more likely to reduce host immune responses.…”
Section: Immunocompatibility Of Engineered Tissue or Organ‐based Implantsmentioning
confidence: 99%